Digital Entrepreneurship in Africa How a Continent Is Escaping Silicon Valley's Long Shadow - Friederici, Nicolas (The MIT Press, 2020)
The hope and hype about African digital entrepreneurship, contrasted with the reality on the ground in local ecosystems. In recent years, Africa has seen a digital entrepreneurship boom, with hundreds of millions of dollars poured into tech cities, entrepreneurship trainings, coworking spaces, innovation prizes, and investment funds. Politicians and technologists have offered Silicon Valley-influenced narratives of boundless opportunity and exponential growth, in which internet-enabled entrepreneurship allows Africa to "leapfrog" developmental stages to take a leading role in the digital revolution. This book contrasts these aspirations with empirical research about what is actually happening on the ground. The authors find that although the digital revolution has empowered local entrepreneurs, it does not untether local economies from the continent's structural legacies. Drawing on a five-year research project, the authors show how entrepreneurs creatively and productively adapt digital technologies to local markets rather than dreaming of global dominance, achieving sustainable businesses by scaling based on relationships and customizing digital platform business models for African infrastructure challenges. The authors examine African entrepreneurial ecosystems; show that African digital entrepreneurs have begun to form a new professional class, becoming part of a relatively exclusive cultural and economic elite; and discuss the impact of Silicon Valley's mythologies and expectations. Finally, they consider the implications of their findings and offer recommendations to policymakers and others.